THE USE OF Er,Cr: YAG IN THE TREATMENT OF PERI-IMPLAANTITIS - Forna Consuela Norina; Perez Javier; Pilipili Charles; Songo Florent; Forna Agop Doriana (Romanian Society of Oral Rehabilitation, 2018)
40 patients with implant-prosthetic restorations and diagnosed with at least one implant affected by moderate or severe peri-implantitis were selected from Learning Centre "M.Kogalniceanu" of Dental Medicine Faculty, U.M.F."Grigore T.Popa" Iasi and a private practice. Patients were randomly divided in test group (laser-assisted treatment, flap procedure) and control (mechanical debridement, flap procedure). In the test group, the conventional treatment protocol was assisted by laser therapy (2940nm Er,Cr:YAG laser) . It was recorded (for 7 days post-operatively) the evolution of the next clinical parameters: VAS indices (pain intensity); patients' disconfort; healing time. Results. In the laser-irradiated group, VAS indices decreased from 2,8 (T0), to 2,4 at 24 h post-operatively, and 0,6 at 48 hours post-operatively. The mean values of healing time are significantly lower (6,5 days) comparing with control (8,5 days). Conclusion. Laser bio-stimulation in peri-implantitis has positive effects on inflammatory processes in peri-implant tissues and accelerate healing processes.